Impact of gamification on glycaemic control among patients with type 2 diabetes mellitus: a systematic review and meta-analysis of randomized controlled trials. Issue 3 (18th October 2021) - Kaihara, Toshiki; Intan-Goey, Valent; Scherrenberg, Martijn; Falter, Maarten; Frederix, Ines; Akashi, Yoshihiro; Dendale, Paul
Abstract: Aims : The prevalence of type 2 diabetes mellitus (T2DM) is very high and still rising. Optimal medical therapy and lifestyle management are essential in reducing the long-term complications of T2DM. Gamification, which is the use of design elements, and characteristics of games in a non-gaming context, is an innovative approach to improve healthy behaviour. It thereby could be able to improve glycaemic control in T2DM. The aim of this systematic review and meta-analysis is to evaluate the effect of gamification on glycaemic control expressed by haemoglobin A1c (HbA1c) levels in T2DM patients. Methods and results : All articles from 2000 to 2021 were searched in electronic databases (PubMed, Cochrane Library, Embase). The total number of patients was 704. The rate of male participants and their mean ages ranged, respectively, from 46% to 94% and 60 to 63 years. Inclusion criteria were randomized controlled trials of T2DM management using gamification which included HbA1c as an outcome measure. A meta-analysis was performed. After removing duplicates, 129 articles were screened and a total of 3 articles corresponding to the inclusion criteria were identified. Haemoglobin A1c was significantly reduced [mean difference −0.21; 95% confidence interval (−0.37 to −0.05); P = 0.01; I 2 = 0%] in the intervention group using gamification as compared to the control group. Conclusion : Gamification has a positive effect on glycaemic control expressed by HbA1c changes in patients with T2DM. However, only three studies were included in this review. More research is needed to confirm the effectiveness of gamification in T2DM. Graphical Abstract: